2022
DOI: 10.3390/su14020716
|View full text |Cite
|
Sign up to set email alerts
|

Token Economy for Sustainable Education in the Future: A Scoping Review

Abstract: This research aims to examine the use of a token economy for education sustainability. It presents a recent review and evaluation of the token economy used among young learners and learners with special needs for behavior management and learning engagement in teaching. Online articles from Google Scholar, ERIC, and UKMLibrary were used. The terms used for reviewing the articles were token economy, token systems, positive reinforcement, and rewards. The scoping review protocol was used for this study. A total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
(41 reference statements)
0
5
0
1
Order By: Relevance
“…Jika token ekonomi diterapkan dengan baik maka dapat menjadi fasilitator dalam mengubah perilaku dan meningkatkan prestasi akademik siswa. 36…”
Section: Penelitian Ini Menggunakan Pendekatan Kuantitatif Dengan Jen...unclassified
“…Jika token ekonomi diterapkan dengan baik maka dapat menjadi fasilitator dalam mengubah perilaku dan meningkatkan prestasi akademik siswa. 36…”
Section: Penelitian Ini Menggunakan Pendekatan Kuantitatif Dengan Jen...unclassified
“…Among RADAR's many activities, one of the most appreciated interventions by patients/parents is an intervention based on the principles of the token economy ( 59 61 ); this method has already proven its effectiveness in other contexts ( 62 64 ). Over the last 4 years, we have built an autonomous system on understanding the feasibility of a method based on the principle of reward and “reward” in RT.…”
Section: Art Creativity and Technologies In Cancer Treatment: The Ita...mentioning
confidence: 99%
“…The use of economic tokens in education is not new and is generally used to change unwanted behavior (Yahya et al, 2016). Studies from Fiksdal (2014), Ahkam et al (2020), Ismail (2022) and Tan et al (2022) have shown that economic tokens are beneficial to increase students' concentration, excitement and interest.…”
Section: Introductionmentioning
confidence: 99%